Design and implementation of a DSP based digital controller for a DC-DC converter - Mohd Faridun Naim, Tajuddin; Rahim, N. A.; Ismail, Daut (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/